Architectural vulnerability during wars, natural disasters, and technological threats as a factor in the loss of sacred heritage - HYRIA, Valentyn (Ways to Improve Construction Efficiency, 2025)
Sacred architecture is one of the most valuable carriers of humanity’s spiritual and cultural memory, yet it demonstrates the greatest vulnerability during periods of war, natural disasters, and technological threats. The destruction of temples, monasteries, and sanctuaries leads not only to the loss of unique architectural forms but also disrupts the spiritual continuity of cultural identity. Architectural vulnerability under such conditions is considered a multifactorial process, in which physical, natural, social, and symbolic factors interact. Wars test not only the structural integrity of buildings but also the spiritual resilience of societies. The deliberate destruction of sacred sites becomes an act of cultural genocide aimed at erasing collective memory. Natural disasters, in turn, reveal the material aging of temples and the technological limitations of past eras, while technological threats – pollution, vibrations, and climate fluctuations – cause hidden yet continuous structural degradation. The study emphasizes that the preservation of sacred heritage has both material and spiritual dimensions. Physical restoration of temples is impossible without resacralization of the space – restoring its original meaning through community participation, ritual practices, and the revival of historical memory. Several analytical models for assessing architectural resilience are proposed, including an integral vulnerability index, an equation of the structural-semantic energy of a temple, and a model of spiritual regeneration. Particular attention is given to the role of digital technologies – 3D scanning, laser photogrammetry, and digital twins – that make it possible to record the condition of sacred structures and create precise virtual replicas to preserve them in the event of destruction. Thus, digital representation becomes a new form of memory that extends the life of architecture in virtual space. Architectural vulnerability emerges not only as a characteristic of physical structure but also as an indicator of a society’s spiritual maturity. Where preservation occurs – even in digital form – culture demonstrates its responsibility and awareness of its historical continuity. The preservation of sacred architecture is, therefore, an act of spiritual resistance that affirms humanity’s dignity and its capacity for renewal despite destruction.